Formal Methods for Dynamic Power Management - Gupta, Rajesh K.; Irani, Sandy; Shukla, Sandeep K. (International Conference on Computer Aided Design: Proceedings of the 2003 IEEE/ACM international conference on Computer-aided design; 09-13 Nov. 2003, 2003)
Dynamic Power Management or DPM refers to the problem ofjudicious application of various low power techniques based onruntime conditions in an embedded system to minimize the totalenergy consumption.To be effective, often such decisions takeinto account the operating conditions and the system-level designgoals.DPM has been a subject of intense research in thepast decade driven by the need for low power in modern embeddeddevices.We present an overview of the formal methods thathave been explored in solving the system-level DPM problem.We show how formal reasoning frameworks can potentially unifyapparently disparate DPM techniques.